Biological protection of sugar beet sowings from beet nematode - Doronin, V.; Kalatur, К.; Kravchenko, Yu.; Drуha, V.; Suslyk, L.; Honcharuk, H.; Polovynchuk, О.; Doronin, V. Jr. (Quarantine and plant protection, 2022)
Goal. To identify the efficiency of the bionematicide Clariva 156, FS (spores of the bacterium Pasteuria nishizawae, strain Pn 1, 0.02 l/seed unit) against beet nematode in sugar beet sowings. Methods. Laboratory, field. The research was carried out in Vinnytsia region in the years 2017—2019. Small-scale experiments were established in a natural invasive background. To determine the number of beet nematodes, soil samples were taken and analyzed before sowing and before harvesting sugar beet, as well as after the development of the first generation of the parasite. The accounting of sugar beet yield was carried out by weighing all root crops from each plot and counted per hectare of sowing. The sugar content of roots was determined on the on-stream line Venema by the method of cold-water digestion. Results. The use of bionematicide Clariva 156, FS allowed to reduce the number of the first generation of beet nematode by 27.7—35.3% (1.5 times) compared to the density of its population before sowing sugar beet. It is noted that the decrease in the number of parasites in the soil in the first half of the growing season had a positive effect on crop productivity. In particular, in the treatments where the seeds were treated with the biological preparation Clariva 156, FS, root yield increased by 2.3—12.6 t/ha, and the sugar collection increased by 0.5—1.9 t/ha, compared to the treatments without nematicide. Conclusions. Given the widespread and significant damage caused by the beet nematode to sugar beet sowings, the problem of protecting this crop from heteroderosis is still relevant. Its solution begins with a nematological survey of fields and ends with the introduction of an integrated control system, an important element of which is the use of biological methods. The obtained results prove that treatment of sugar beet seeds with bionematicide Clariva 156, FS gives the chance to reduce number of the first generation of beet nematode in sugar beet sowings up to 35%.